2020
DOI: 10.1590/2318-0331.252020190050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study between turbulence models in curved channels

Abstract: This paper presents a comparative study between results obtained in two-dimensional computational simulations performed with three different turbulence models: constant viscosity; Elder Model and k˗Ꜫ Model. The simulations were performed using the software Telemac 2D. These results were compared to data obtained from a study in experimental channel with trapezoidal cross-section and composed of straight stretches and curves. The main objective of this comparison is to explore how turbulence models affect the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Turbulence in meandering rivers has also been studied via modeling approaches, including models based on the RANS equations (e.g., Almeida & Ota, 2020; Fischer‐Antze et al., 2009; Gholami et al., 2014; Kim et al., 2020; Rameshwaran & Naden, 2004; Wormleaton & Ewunetu, 2006), which rely on the performance of the turbulence models. More recently, the impact of turbulence closure schemes on the flow in curved channels has been investigated (e.g., Almeida & Ota, 2020; Kim et al., 2020). However, few studies have used high‐resolution Lagrangian field observations to validate a numerical model and to explore the flow‐following distributions of turbulence along a river.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Turbulence in meandering rivers has also been studied via modeling approaches, including models based on the RANS equations (e.g., Almeida & Ota, 2020; Fischer‐Antze et al., 2009; Gholami et al., 2014; Kim et al., 2020; Rameshwaran & Naden, 2004; Wormleaton & Ewunetu, 2006), which rely on the performance of the turbulence models. More recently, the impact of turbulence closure schemes on the flow in curved channels has been investigated (e.g., Almeida & Ota, 2020; Kim et al., 2020). However, few studies have used high‐resolution Lagrangian field observations to validate a numerical model and to explore the flow‐following distributions of turbulence along a river.…”
Section: Introductionmentioning
confidence: 99%
“…Surface slope and secondary flows are often well predicted using a k‐ ϵ turbulence closure scheme (e.g., Demuren & Rodi, 1986; Parsapour‐Moghaddam & Rennie, 2017; Wormleaton & Ewunetu, 2006) even for strongly curved bends (Gholami et al., 2014). These studies have also shown that different turbulence models predicted slightly different simulated flow; for instance, Almeida and Ota (2020) demonstrated that the k‐ ϵ closure scheme could reliably reproduce the velocity all along the domain in their 2D‐simulation of a curved channel whereas the other model they tested, the Elder Model (an algebraic model), could not reproduce the velocity field both in sections of high curvature and in straight portions of the channel. Similarly, other studies have found that 3D velocity structure (and hence predictions of solute transport) are sensitive to the selected turbulence closure scheme, mainly due to the difficulty in perfectly reproducing the flow separation (Kim et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation